2020
DOI: 10.17344/acsi.2020.6028
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Biological Screening of Novel 1,5-Diphenyl-3-(4-(trifluoromethyl)phenyl)-2-pyrazoline Derivatives

Abstract: 1-Phenyl-5-substituted-3-(4-(trifluoromethyl)phenyl)-4,5-dihydro-1H-pyrazole derivatives were synthesized from chalcone derivatives. The structures of compounds were characterized by IR, 1H NMR spectroscopic methods and elemental analysis. All compounds were evaluated for their in vitro antioxidant activity using DPPH and ABTS methods, anti-inflammatory activity using lipoxygenase inhibitory method and antidiabetic activity using the α-glucosidase inhibitory method. Especially, pyrazoline derivatives exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…It is possible for drug candidates to succeed in phase studies with good lipophilicity, water solubility, physicochemical and pharmacokinetics properties. 16 Therefore, we evaluat- ed the druglikeness properties such as Lipinski, Ghose, Veber, Egan and Muegge filters of all synthesized compounds. The results showed that the majority of all compounds did not violate these filters.…”
Section: In Silico Admet Resultsmentioning
confidence: 99%
“…It is possible for drug candidates to succeed in phase studies with good lipophilicity, water solubility, physicochemical and pharmacokinetics properties. 16 Therefore, we evaluat- ed the druglikeness properties such as Lipinski, Ghose, Veber, Egan and Muegge filters of all synthesized compounds. The results showed that the majority of all compounds did not violate these filters.…”
Section: In Silico Admet Resultsmentioning
confidence: 99%
“…Chalcone is an important chemo type that has attracted great research interest for decades due to the abundant natural chalcone-based compounds, the easy synthesis and derivatization, and most importantly, the diverse biological activities of various chalcone-based compounds. [1][2][3][4][5][6] The well documented biological activities of chalcones include anti-HIV, 7 antibacterial, 8 anti-cancer and antioxidant, [9][10][11] antituberculosis agents, 12 anti-prolif-erative, 13 antiplatelet, 14,15 and antimalarial. 16,17 Numerous studies have attempted to elucidate the mechanisms of action and target interactions responsible for these biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…The Claisen-Schmidt condensation reaction, one of the most widely used chalcone synthesis methods, was used in the synthesis of compounds in this article by using sodium/potassium hydroxide. [28][29][30][31][32][33][34][35][36] The base-cata-Sirka et al: (E)-1-(4-Hydroxyphenyl)-3-(substituted-phenyl) ... lysed other method of chalcone synthesis include Claisen-Schmidt reaction. 37 The acid catalyzed methods that have been used to synthesize chalcones includes Friedel-Crafts acylation, 38 silica-sulfuric acid, 39 dry HCl, 40,41 boron trifluoride-diethyletherate (BF 3 -Et 2 O), 42 Aldol condensation, 43 Suzuki coupling reaction, 44 Julia-Kocienski olefination 45 and Wittig reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pyrano-[2,3-c]-pyrazoles are the subject of modern biochemistry that is growing rapidly and has stimulated extensive applications. Chief among these are multiple pharmacological and biological properties, such as antioxidant, antibacterial, anti-molluscicidal, analgesic, antiviral potential, and inhibitors of human checkpoint kinase-1 [9]. Upon an extensive literature review, it was confirmed that the wide-range of pyrano-[2,3-c]-pyrazoles activities are linked to the structural base core of the condensed pyrane and pyrazole [10].…”
Section: Introductionmentioning
confidence: 99%